Association Between Sleep and Motoric Cognitive Risk Syndrome Among Community-Dwelling Older Adults: Results From the China Health and Retirement Longitudinal Study - Weihao Xu (Frontiers Media S.A., 2021)
Background: Sleep is increasingly recognized as an important lifestyle contributor to health; however, its relationship with Motoric cognitive risk syndrome (MCR) is still unclear. The present study aimed to examine the associations between sleep duration, sleep quality, and MCR among community-dwelling Chinese older adults.Methods: We recruited 5,387 participants aged ≥60 years from the China Health and Retirement Longitudinal Study (CHARLS). Sleep-related variables including night sleep duration and sleep quality were assessed via self-reported questionnaires. MCR syndrome was defined as cognitive complaints and slow gait speed without dementia or impaired mobility. Multivariate logistic regression analysis was performed to explore the associations between sleep-related variables and MCR after controlling for all potential confounders including demographic characteristics, lifestyle factors, and comorbidities.Results: We found that sleep duration was significantly associated with MCR, and the multivariate-adjusted odds ratios (OR) were highest for those with the shortest (<6 h OR = 1.55, 95% CI = 1.18–2.04) and longest (≥10 h OR = 1.73, 95% CI = 1.03–2.91) sleep durations. Moreover, an increasing frequency of self-perceived poor sleep quality was significantly associated with MCR in the adjusted model (3–4 days OR = 1.58, 95% CI = 1.16–2.17; 5–7 days OR = 1.81, 95% CI = 1.37–2.40).Conclusions: Our study indicated an inverted U-shaped association between night sleep duration and MCR. Poor sleep quality was also associated with higher odds of MCR in community-dwelling Chinese elders. Longitudinal studies with a larger population size are needed to establish causality in the future and further explore potential action mechanisms.